In vitro ruminal fermentation characteristics and utilisable CP supply of sainfoin and birdsfoot trefoil silages and their mixtures with other legumes. (31st August 2016) - Grosse Brinkhaus, A.; Wyss, U.; Arrigo, Y.; Girard, M.; Bee, G.; Zeitz, J. O.; Kreuzer, M.; Dohme-Meier, F.
Abstract : The extensive protein degradation occurring during ensiling decreases the nutritive value of silages, but this might be counteracted by tannins. Therefore, silages from two legume species containing condensed tannins (CT) – sainfoin (SF) and birdsfoot trefoil (two cultivars: birdsfoot trefoil, cv. Bull (BTB) and birdsfoot trefoil, cv. Polom) – were compared for their in vitro ruminal fermentation characteristics. The effect of combining them with two CT-free legume silages (lucerne (LU) and red clover (RC)) was also determined. The supply of duodenally utilisable CP (uCP) in the forages was emphasised. The legumes were each harvested from three field sites. After 24 h of wilting on the field, the legumes were ensiled in laboratory silos for 86 days. Proximate constituents, silage fermentation characteristics, CT content and CP fractions were determined. Subsequently, silage samples and 1 : 1 mixtures of the CT-containing and CT-free silages were incubated for 24 h in batch cultures using ruminal fluid and buffer (1 : 2, v/v). Each treatment was replicated six times in six runs. The effects on pH, ammonia and volatile fatty acid concentrations, protozoal counts, and total gas and methane production were determined. uCP content was calculated by considering the CP in the silage and the ammonia in the incubation fluid from treatments and blanks. Statistical evaluation compared data from single plants alone and together with that from the mixtures. Among treatments, SF silage contained the least CP and the most CT. The non-protein nitrogen content was lower, favouring neutral detergent soluble and insoluble protein fractions, in the SF and RC silages. Absolute uCP content was lowest in SF and SF mixtures, although the ratio to total CP was the highest. In comparison with LU, the ammonia concentration of the incubation fluid was lower for SF, RC and BTB and for the mixture of SF with LU. The total gas and methane production was similar among the treatments, and the total volatile fatty acid production was decreased with the CT-containing legumes. Protozoal count was increased with the mixtures containing LU and either SF or BTB compared with single LU. In conclusion, compared with the other legumes, SF and RC have similar advantages as they show limited proteolysis during ensiling. In addition, SF supplies more uCP relative to total CP. The CT-containing legumes also differed in their effect on ruminal fermentation and ammonia formation, probably because of their different CT contents. Thus, SF and its mixtures appear promising for improving the protein utilisation of ruminants.